Set7/9, a methyltransferase, regulates the thermogenic program during brown adipocyte differentiation through the modulation of p53 acetylation. (15th August 2016) - Son, Min Jeong; Kim, Won Kon; Park, Anna; Oh, Kyoung-Jin; Kim, Jeong-Hoon; Han, Baek Soo; Kim, Il Chul; Chi, Seung-Wook; Park, Sung Goo; Lee, Sang Chul; Bae, Kwang-Hee
Abstract: Brown adipose tissue, which is mainly composed of brown adipocytes, plays a key role in the regulation of energy balance via dissipation of extra energy as heat, and consequently counteracts obesity and its associated-disorders. Therefore, brown adipocyte differentiation should be tightly controlled at the multiple regulation steps. Among these, the regulation at the level of post-translational modifications (PTMs) is largely unknown. Here, we investigated the changes in the expression level of the enzymes involved in protein lysine methylation during brown adipocyte differentiation by using quantitative real-time PCR (qPCR) array analysis. Several enzymes showing differential expression patterns were identified. In particular, the expression level of methyltransferase Set7/9 was dramatically repressed during brown adipocyte differentiation. Although there was no significant change in lipid accumulation, ectopic expression of Set7/9 led to enhanced expression of several key thermogenic genes, such as uncoupling protein-1 (UCP-1), Cidea, peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α), and PR domain containing 16 (PRDM16). In contrast, knockdown of endogenous Set7/9 led to significantly reduced expression of these thermogenic genes. Furthermore, suppressed mitochondrial DNA content and decreased oxygen consumption rate were also detected upon Set7/9 knockdown. We found that p53 acetylation was regulated by Set7/9-dependent interaction with Sirt1. Based on these results, we suggest that Set7/9 acts as a fine regulator of the thermogenic program during brown adipocyte differentiation by regulation of p53 acetylation. Thus, Set7/9 could be used as a valuable target for regulating thermogenic capacity and consequently to overcome obesity and its related metabolic diseases. Graphical abstract: Highlights: The expression level of Set7/9 was decreased during brown adipocyte differentiation. Ectopic expression of Set7/9 led to enhanced expression of key thermogenic genes. Knockdown of Set7/9 led to significantly reduced expression of key thermogenic genes. Set7/9 acts as a fine regulator of the thermogenic program during brown adipogenesis.